Spatio-Temporal Analysis of Noise in Selected Areas of Oyo Township - A. Tajudeen, Oladokun,; Aderibigbe, N. B (Kashere Journal of Education, 2021)
Noise is an important environmental problem in major cities of tropical African countries with Nigeria not exempted. The study adopted a quantitative measurement of noise at selected sites having heterogeneous spatial characteristics. The data collected were analyzed using totals, means, t-test and a two-way ANOVA. The study showed that noise is a feedback mechanism stemming from myriads of urbanization and industrialization processes, poor urban planning, social functions, vehicular activities (hooting), household activities, hawking and other commercial activities of the recent times. The study also showed that noise level is functionally related to temporal and spatial characteristics of places. All these have resulted in vulnerability and exposure of the cities dwellers to noise related health impairment despite the presence of some health care centres. The immediate responses known to have followed excessive noise in these areas are hearing loss, sleeping disorder, annoyance, communication impairment, health related problems like cardiovascular diseases, temporary or permanent deafness and the likes. It is hereby recommended that adequate and timely environmental education be organized for people to have a change of attitude towards noise level reduction in particular and environmental pollution in general